FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KECENDERUNGAN KECURANGAN (FRAUD): PERSEPSI PEGAWAI PEMERINTAHAN DAERAH KOTA BOGOR - Didi, Didi; Kusuma, Indra Cahya (Jurnal Akuntansi dan Keuangan Indonesia, 2018)
This study aims to examine the effect of distributive justice, procedural justice, internal control, enforcement of regulations, organizational commitment and organizational culture on the fraudulent tendencies. Variables are developed based on Donald Cressey’s fraud triangle theory (1953). The population in this study is the government agencies in the city of Bogor. Research sample is determined using a quota sampling method with the criteria of employees responsible for the financial management of each agency. The data in this research is obtained by distributing questionnaires to 143 respondents on 34 government agencies in the city of Bogor. The results prove that the internal control and enforcement of regulations influence fraudulent tendencies. Meanwhile, distributive justice, procedural justice, organizational commitment and organizational culture have no significant effect on fraudulent tendencies.